Family Communication during the 2019 Corona Virus Disease (Covid-19) Pandemic - Puri Kusuma Dwi Putri (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
Conversations among parents and children about the Corona Virus Disease 2019 (Covid-19) and how to prevent the transmission can reduce anxiety and a fear of children about the situation around them. Family communication refers to the verbal and non-verbal word that is happened between family members. Communication involves the ability to pay attention to others about what they think and feel. Communication does not only involve verbal words, but also listens to each other. The purpose of this article was to find out how parent-child communication during the Covid-19 pandemic. The method of this article used literature studies from books, scientific journals, and the internet websites. The results showed that healthy families communicated effectively well, while families with unhealthy relationships had poor communication. The effective communication in the family can be improved by family members through the quality of their relationships, namely frequent communication, communicating clearly and directly, being an active listener, communicating openly and honestly, thinking about people with whom to communicate, paying attention to non-verbal messages, communicating positively, and focus on family strengths. It is better if parents can increase their interaction with their children regarding Covid-19 messages during the pandemic, because it can make an impact on the relationship between parent-child.